2022
DOI: 10.3389/fcell.2022.794198
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Effects of Kefir Peptides on Hemophilia-Induced Osteoporosis in Mice With Deficient Coagulation Factor VIII

Abstract: Osteoporosis is a clinically prevalent comorbidity in patients with hemophilia. A preventive effect of kefir peptides (KPs) on postmenopausal osteoporosis has been proved. The aim of this study was to evaluate the therapeutic effect of KPs for the treatment of osteoporosis in coagulation factor VIII (FVIII) gene knockout mice (F8KO), a model of hemophilia A. In this study, male F8KO mice at 20 weeks of age were orally administered different doses of KPs for 8 weeks. The therapeutic effects of KPs were shown in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
15

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 39 publications
0
4
0
15
Order By: Relevance
“…Concomitantly, KP treatment improved BMD and microarchitecture in trabecular ( Figure 4 ) and cortical bones ( Figure 5 ) with an increase in the circulating bone formation marker P1NP and a reduction in the resorption marker CTX1 ( Figure 6 ), which showed that bone remodeling favored bone formation in KP-treated ApoE −/− mice. In fact, KPs have repeatedly demonstrated bone-protective benefits in our earlier animal models of osteoporosis caused by estrogen depletion ( Chen et al, 2015 ; Tu et al, 2020 ), hemophilia ( Yen et al, 2022 ), and vitamin C insufficiency ( Chang et al, 2022 ), and rats with glucocorticoid-induced osteoporosis ( de Vasconcelos et al, 2022 ). We recently demonstrated that KPs promoted osteoblastic differentiation and bone mineralization while inhibiting RANKL-induced osteoclastic differentiation and bone resorption in vitro ( Chang et al, 2022 ), and treatments with KPs eventually lowered the circulating RANKL/OPG ratio in vivo ( Chang et al, 2022 ; Yen et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Concomitantly, KP treatment improved BMD and microarchitecture in trabecular ( Figure 4 ) and cortical bones ( Figure 5 ) with an increase in the circulating bone formation marker P1NP and a reduction in the resorption marker CTX1 ( Figure 6 ), which showed that bone remodeling favored bone formation in KP-treated ApoE −/− mice. In fact, KPs have repeatedly demonstrated bone-protective benefits in our earlier animal models of osteoporosis caused by estrogen depletion ( Chen et al, 2015 ; Tu et al, 2020 ), hemophilia ( Yen et al, 2022 ), and vitamin C insufficiency ( Chang et al, 2022 ), and rats with glucocorticoid-induced osteoporosis ( de Vasconcelos et al, 2022 ). We recently demonstrated that KPs promoted osteoblastic differentiation and bone mineralization while inhibiting RANKL-induced osteoclastic differentiation and bone resorption in vitro ( Chang et al, 2022 ), and treatments with KPs eventually lowered the circulating RANKL/OPG ratio in vivo ( Chang et al, 2022 ; Yen et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, KPs have repeatedly demonstrated bone-protective benefits in our earlier animal models of osteoporosis caused by estrogen depletion ( Chen et al, 2015 ; Tu et al, 2020 ), hemophilia ( Yen et al, 2022 ), and vitamin C insufficiency ( Chang et al, 2022 ), and rats with glucocorticoid-induced osteoporosis ( de Vasconcelos et al, 2022 ). We recently demonstrated that KPs promoted osteoblastic differentiation and bone mineralization while inhibiting RANKL-induced osteoclastic differentiation and bone resorption in vitro ( Chang et al, 2022 ), and treatments with KPs eventually lowered the circulating RANKL/OPG ratio in vivo ( Chang et al, 2022 ; Yen et al, 2022 ). Although serum RANKL and OPG levels were not measured at the end of this study, it was speculated that KP treatment could lower the serum RANKL/OPG ratio in the current ApoE −/− model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study showed that thrombin receptor deficiency leads to a decrease in RANKL/OPG ratio which was associated with a high bone density phenotype ( Tudpor et al, 2015 ). Conversely, a significant increase in the RANKL/OPG ratio and signs of osteoporosis were noticed in a mouse model of hemophilia ( Yen et al, 2022 ). Moreover, OPG may play a role in regulating thrombus formation by binding to Von Willebrand factor (VWF), an essential factor for platelet adhesion ( Wohner et al, 2022 ).…”
Section: Rank/rankl/opg In Cardiac and Smooth Musclesmentioning
confidence: 99%
“…A osteoporose se caracteriza por uma desordem osteometabólica sistêmica que desencadeia redução da densidade mineral óssea (DMO) e deterioração da microarquitetura óssea, no entanto, sua etiologia varia de acordo com o mecanismo da perda óssea (YEN et al, 2022). Dessa forma, ela pode ser classificada em primária ou secundária.…”
Section: Introductionunclassified